Ovarian cancer onset across different BRCA mutation types: a view to a more tailored approach for BRCA mutated patients. Issue 2 (29th December 2022) - Marchetti, Claudia; Ataseven, Beyhan; Cassani, Chiara; Sassu, Carolina Maria; Congedo, Luigi; D'Indinosante, Marco; Cappuccio, Serena; Rhiem, Kerstin; Hahnen, Eric; Lucci Cordisco, Emanuela; Arbustini, Eloisa; Harter, Philipp; et al.
Abstract : Objective: To evaluate the role of different specific types of germline breast cancer susceptibility BRCA mutations on the age of onset of high grade serous ovarian cancer. Methods: This was a multicenter, international, retrospective cohort of 474 patients diagnosed with recurrent or newly diagnosed high grade serous ovarian cancer, with known germline mutations in BRCA1/2 genes, treated between January 2011 and December 2020 in three academic centers in Europe. Patients were classified into four groups related to the type of BRCA1/2 genes mutation: frameshift, missense, nonsense, and splicing. Data from patients with splicing mutations were removed from the analysis because of the small numbers. The other three groups were compared. Results: Excluding the 29 patients with a splicing mutation, 474 patients were enrolled: 309 (65.2%) with frameshift mutations, 102 (21.5%) with nonsense mutations, and 63 (13.3%) with missense mutations. The BRCA1 gene was affected in 324 (68.4%) cases, while BRCA2 was involved in 150 (31.6%) women (p=0.06). We found a difference of more than 5 years in the age of onset of high grade serous ovarian cancer between BRCA1 and BRCA2 patients (mean 53.3 years vs 58.4 years; p=0.001), with a mean age of 55.1 years. Patients with nonsense germline mutations had the youngest age of onset, while women with frameshift mutations had the oldest age of onset of high grade serous ovarian cancer (mean 52.2 years vs mean 55.9 years), both in the BRCA1 and BRCA2 subgroups. There was no statistically significant difference in age of onset between early and advanced groups (mean 55.8 years vs 55.0 years; p=0.55). Conclusion: Different types of germline BRCA mutations could determine different ages for onset of high grade serous ovarian cancer. If confirmed in larger series, this finding might have a clinical impact, potentially leading to a more tailored approach for risk reducing surgery for the prevention of high grade serous ovarian cancer.